The increasing importance of teaching and learning geoeconomics in a meaningful context - Nicoleta Vasilcovschi (CES Working Papers, 2022)
Significant changes of national and global events require adequate responses not just from governments, but as well from the educational areas. The end of the Cold War in 1990, followed by the Economic Crisis of 2007-2008, and the Pandemic Crisis of 2020 were global challenges that increased the importance of geoeconomic field and the need to study Geoeconomics nowadays as an interdisciplinary subject, as a discipline that exercises crucial roles internationally, requiring learners to study it in a meaningful context. In the future, present learners of Geoeconomics will work for countries that will use their strategic positions to access resources and promote their economic interests. They will analyze different interconnections between geography and economics that are transforming the world and promoting a global demand for labour force flexibility. They will be workers that will migrate and study to find their place and role in this evolving geoconomic system. In the present dynamic geoeconomic context, the field of education remains the key to prepare future generations to use a critical thinking approach when deciding how to apply internationally geoeconomic knowledge and skills. This research paper presents different aspects of Geoeconomics as a discipline and shows several steps that can be followed in order to teach and learn an interdisciplinary subject in a meaningful context, using an inclusive education and a cooperative learning approach. In fact, this research paper contains several authentic activities that can be used in the process of teaching and learning Geoeconomics, online or offline, and, more broadly, evaluates the needs of students and the role of lecturers in the process of international education, showing as well different techniques that can be used to prevent plagiarism. This research paper also includes an analysis of the process of meaningful teaching, its features, and the challenges that students can have with studying interdisciplinary subjects within the Social Sciences area.
Keywords: 330; Geoeconomics; meaningful teaching context; cooperative learning; plagiarism prevention; inclusive education; authentic learning activities; knowledge power